Pengaruh Substitusi Abu Batu (Quarry Dust) Pada Nilai CBR Laboratorium Untuk Stabilitas Subgrade Timbunan - Adwiyah Asyifa; Syafi’ul Umam (Semesta Teknika, 2016)
Quarry dust (dust mine) is a non-plastic materials from the rest of quarry stone crusher machine in range size are  0 - 5 mm. Production of quarry dust in Indonesia is very abundant. A stone crusher in the maximum work can be produced quarry dust up to 4 tons per hour. The use of quarry dust now is still less optimal. Its only used as a filler in the surface layer of pavement. So that , there are more innovation in use of  quarry  dust  to balance between produce and use. One uses the quarry dust  isfor soil stabilization.Soil stabilization is the engineering effort to improve the quality of the soil is not good and improve the quality of the soil that has actually been quite good.In pavement structural design, not all subgrade base having a good CBR value, it was low in CBR rate and it must be replacement, repair or soil stabilization. This  experimental study was conducted  in Soil Mechanics Laboratory Departement Civil Engineering University Technology Yogyakarta. Object research aresoil water content  and soil density to determine the optimum soil water content. This amount water will added in to mixture of stone dust (quarry dust) 0%, 5%, 10%, 15 % and 20% and this variation test will be aging for 48 hours. Results this research indicates that5% quarry dust added to the mixture will gave the optimum CBR amounted to 26.20%. That amount represents an increase of 19.01% from the design CBR native land by 22%.